Prototype of Automatic Monitoring and Control System for Water Supply, Acidity, and Nutrition in Internet of Things Based DFT Hydroponics - Andre Heri Bakriansyah; Muhammad Daud; Taufiq Taufiq; Asran Asran (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
In the hydroponic deep flow technique (DFT) system, in general, the measurement of water quality parameters is still done manually and because of this it often results in delays in adding nutrients, causing yellowing of plants. This study aims to design and realize a prototype system for automatic monitoring and replenishment of water supply, pH (acidity), and nutrients in DFT hydroponics based on Arduino UNO and the internet of things. The system is built with Arduino UNO, pH sensor, TDS sensor, HC-SR04 sensor, DC water pump, NodeMCU, ThingSpeak and Blynk applications. The results showed that the system prototype was able to work well. The difference in the measurement results by the sensor compared to the reference measuring instrument is relatively small, namely the difference in pH 2.058%, TDS 0.835%, distance 0.255% and pH control 0.43%, TDS 0.404%, and volume 0.69%. The system prototype has succeeded in maintaining the pH level of the solution, the TDS of the solution, and the quality of the water in the system. Pada system hidroponik deep flow technique (DFT), secara umum pengukuran parameter-paramter kualitas air masih dilakukan secara manual dan karenanya sering mengakibatkan keterlambatan penambahan nutrisi sehingga membuat tanaman menguning. Penelitian ini bertujuan merancang dan merealisasikan prototipe sistem pemantauan otomatis dan pengisian pasokan air, pH (keasaman), dan nutrisi pada hidroponik DFT berbasis Arduino UNO dan internet of things. Sistem dibangun dengan Arduino UNO, sensor pH, sensor TDS, sensor HC-SR04, pompa air DC, NodeMCU, aplikasi ThingSpeak dan Blynk. Hasil penelitian menunjukkan bahwa prototipe sistem mampu bekerja dengan baik. Selisih hasil pengukuran oleh sensor dibandingkan alat ukur referensi relatif kecil yaitu selisih pH 2.058%, TDS 0.835%, jarak 0.255% dan pengendalian pH 0,43%, TDS 0,404%, dan volume 0,69%. Prototipe sistem telah berhasil mempertahankan kadar pH larutan, TDS larutan, dan kualitas air dalam sistem.